Dialectic Lexical Units in the Folklore of the Canadian Ukrainians (Case Study of the First Emigration Wave) (Linguostylistic Studies, 2017)
Canada is a home to the second largest Diaspora of the Ukrainians in the world. The formation process of the Ukrainian emigrants’ community in Canada has been gradual. It correlates with the three main stages of the emigration process. According to the historians the first Ukrainians, pursued by the hardships and troubles in their homeland, settled on the territory of Canada in 1891. The majority of the first flow of emigrants was represented by the poorest and low-educated strata of the population from the Western Ukraine, demonstrating cultural and linguistic characteristics of those regions. The article analyzes the dialectic vocabulary in the texts of proverbs. These dialect lexemes were recorded by amateur folklorist Volodymyr Plaviuk, when communicating with the Ukrainians who arrived to the North American continent with the first wave of emigrants. The article considers the semantic peculiarities of the detected dialectal nouns, verbs, adjectives, adverbs, interjections, exclamations. It has been revealed that the most representative are the semantic groups of the lexemes, which are used to nominate: 1) actions, processes, states; 2) the character features of a person; 3) persons by family and family ties or by type of their activity or property status; 4) mythical creatures; 5) clothes, ornaments; 6) animals, plants, mushrooms; 7) food, dishes; 8) household vocabulary and others. A separate group is represented by the so-called semantic dialecticisms – words used in a certain dialect, which, having the same sounding and origin with the words of the literary language, have acquired different meanings. The register of dialectal vocabulary reflects the local characteristic features of the carriers of the southern-western dialects. The dialectal core of the proverbs in the language of the south-western dialect, firstly, clearly manifests comprehensive national identity and self-awareness of the first emigrants, and, secondly, proves the necessity of involving multi-ethnic folklore texts into the dialectological research.
Keywords: dialectal vocabulary; folklore; Canada; proverbs; V. Plavіuk; the first emigration wave; South-western dialect; Ukrainian language; nomen; lexical-semantic group; semantic dialecticisms